2021
DOI: 10.1108/ajar-11-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Real earnings management and stock returns: moderating role of cross-sectional effects

Abstract: PurposeThe study aims at investigating the impact of real earnings management (REM) on the cross-sectional stock return after considering the moderating role of market effect, size effect, value effect and momentum effect.Design/methodology/approachThe study uses weekly and monthly data of 3,085 Bombay Stock Exchange listed stocks spanning over twenty years, from January 2000 to December 2019. REM is measured through metrics developed by Roychowdhury (2006), namely, abnormal levels of operating cash flows, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 64 publications
1
12
0
2
Order By: Relevance
“…The result fails to support S. Sayari et al (2013, 51), who found a significantly positive relationship between stock returns and earnings management. The results were all but supportive of the earlier studies that had shown stock returns were negatively significantly related to earnings management (Bansal et al, 2021;Chi & Gupta, 2009). The negative insignificant result is probably indicative of the fact that the stock exchange is unable to reflect earnings management practice (Al Omush et al, 2019, 20).…”
Section: Analysis Of the Results And Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The result fails to support S. Sayari et al (2013, 51), who found a significantly positive relationship between stock returns and earnings management. The results were all but supportive of the earlier studies that had shown stock returns were negatively significantly related to earnings management (Bansal et al, 2021;Chi & Gupta, 2009). The negative insignificant result is probably indicative of the fact that the stock exchange is unable to reflect earnings management practice (Al Omush et al, 2019, 20).…”
Section: Analysis Of the Results And Discussionsupporting
confidence: 83%
“…M. Bansal, A. Ali and B. Choudhary (2021) investigated the real bearing of earnings management on the cross-sectional stock return of the weekly and monthly data of 3,085 firms of the Bombay Stock Exchange from January 2000-December 2019 and showed that investors discounted the stock price when they perceived low-quality real earnings management.…”
Section: Stock Returns and Earnings Managementmentioning
confidence: 99%
“…For instance, Kim and Sohn (2013) find that REM negatively affects the cost of equity capital because investors demand a higher risk premium for REM stocks. In the same vein, under the Indian institutional settings, Bansal et al (2021) find that investors perceive REM as an element of risk, hence demanding a higher premium. Khurana et al (2018) document that REM increases the likelihood of stock price crashes because managers keep poor-performing projects through REM for their self-interests.…”
Section: Literature Reviewmentioning
confidence: 92%
“…In addition, if a company's fundamental performance is solid, then when the company wants to get additional funds from the Right Issue, it can sell its shares at a higher price than the previous IPO. Stock return is a reward from the investment process (Bodie et al, 2010), which consists of two components, namely, (1) return on cash flow from a percentage that measures cash flow in the percentage of related share prices such as purchase price and market price, and (2) Capital Gain, namely transaction profits obtained from the difference between the selling price and the purchase price (Bansal et al, 2021). Stock return is the return that shareholders obtain from the stock investment (Widyakto et al, 2021).…”
Section: Growth In Number Of Investorsmentioning
confidence: 99%